The Consequences of Terrorist and Military Operations in Three Regions of Baghdad, Iraq on Serotonin and Thyroid Function - Jawad, Alaa H (Al-Nahrain Journal of Science, 2018)
In this paper the effect of terrorist and military operations in three regions of Baghdad, Iraq were studied on thyroid gland function and serotonin hormones, in 75 Iraqi individual from (AL-karradah and Abo-Gharib) regions as comparison with Al-jadria (control). The correlation between sera thyroid hormones thyroxine T4, triiodothyronine T3, thyrotropin TSH and serotonin have been indicated‎, the utilization of thyroid hormones as a compelling subordinate treatment for full of feeling issue has been contemplated in the course of recent decades and has been adjusted more than once. Communication of the thyroid and monoamine neurotransmitter frameworks has been recommended as a potential underline component of action. The serotonin framework has been moderately ignored, along these lines; the objective of this article is to audit the writing on the connection between thyroid hormones and the mind serotonin. Our examination proposes a negatively relationship between serotonin and thyroid stimulating hormones (TSH), a positive ‎correlation between serotonin and thyroxine‎, while there were significant positive correlations between serotonin and triiodothyronine. In conclusion, there is powerful confirmation, that the thyroid economy has a balancing sway in the brain serotonin system, thus considerable further investigation will be necessary to understand the role of serotonin in the pathogenesis and high levels in the some regions in Iraq such as AL-karradah and Abo-Gharib.